Complications After endoscopic balloon dilatation of esophageal strictures in children. Experience from a tertiary center in Shiraz – Iran (Nemazee Teaching Hospital) - Mohsen Dehghani, Seyed (2019)
Background: Esophageal stricture is one of the most important complication of the caustic ingestion. Objective: The aim of this study was to evaluate complications of balloon dilatation among children with esophageal stenosis. Material and methods: In this retrospective study 82 children were included. Children who underwent balloon dilatation for esophageal stenosis were included in our study. Duration of study was 14 year starting from 2001. Mean age of the cases was 3.95±0.4 year (Min: 15 days, Max: 14 year). Chart review and telephone calling were the methods of data collection. Data was analyzed using SPSS. Results: In this study, 47% of the patients were male and 53% of the cases were female. Caustic ingestion (33.7%) was the most common etiology for the esophageal stricture. Vomiting (87.8%) was the most common presenting symptom. Among our cases, 76.8% had no compliant after esophageal dilatation. Chest pain was the most common compliant after esophageal dilatation. Response rate was similar among boys and girls. Toddler age had the best treatment response after esophageal dilatation. Conclusion: Among our cases, 76.8% had no post procedural compliant after esophageal dilatation. Esophageal perforation was seen in 4.9% of the cases. Chest pain was the most common post dilatation complication.